Aristotle on μετὰ λόγου capacities and voluntary animal locomotion. Part one: the psychic arguments - Nascimento, Daniel Simão (Revista Archai, 2025)
According to the dominant interpretation of the distinction between capacities that are “without-λόγος” (ἄλογοι) and capacities that are “with-λόγος” (μετὰ λόγου, Metaph. 9.2 1046a34-b2), the latter would be unique to human beings. We can find four arguments in defense of that thesis in the secondary bibliography. This article begins to mount a defense of an alternative reading of Aristotle’s theory that deals with two of these arguments. It will be succeeded by a second article that will deal with the other two arguments and present a positive argument for the alternative reading that tries to make it seem plausible - although not unassailable - in light of its own merits. According to this alternative reading, it is with the framework provided by Aristotle to explain the functioning of bidirectional capacities that we must explain the functioning of the capacity responsible for producing voluntary locomotion in all animals.